All that wobbles isn't necessarily azimuthal anisotropy. Issue 1 (1st December 2019) - Debenham, Helen; Badry, Jennifer; Megebry, Mohamed
Summary: Onshore 3D seismic data is often acquired with rich azimuth coverage by utilising orthogonal shooting (or cross-spread) layouts. This means that azimuthal anisotropy, if present, can be readily observed and its effects on the data can be quantified and accounted for as part of the processing and imaging flow. In this example from the Canning Basin, the data appeared initially to be exhibiting the effects of azimuthal anisotropy. However, with careful handling and honouring of the azimuths of the acquired data during the PreSDM velocity model building, it was possible to correct for most of the variation simply with a laterally variable velocity model, without the need to invoke the presence of azimuthal anisotropy.